Operation-Specific Lexical Consistency Effect in Fronto-Insular-Parietal Network During Word Problem Solving - Ng, Chan-Tat; Lung, Tzu-Chen; Chang, Ting-Ting (Frontiers in Human Neuroscience, 2021)
The practice of mathematical word problem is ubiquitous and thought to impact academic achievement. However, the underlying neural mechanisms are still poorly understood. In this study, we investigate how lexical consistency of word problem description is modulated in adults’ brain responses during word problem solution. Using fMRI methods, we examined compare word problems that include relational statements, such as “A dumpling costs 9 dollars. A wonton is 2 dollars less than a dumpling. How much does a wonton cost?” and manipulated lexical consistency (consistent: the relational term consistent with the operation to be performed, e.g., more–addition/inconsistent: e.g., less–addition) and problem operation (addition/subtraction). We found a consistency by operation interaction in the widespread fronto-insular-parietal activations, including the anterior insula, dorsoanterior cingulate cortex, middle frontal gyrus, and intraparietal sulcus, such that inconsistent problems engaged stronger activations than consistent problems for addition, whereas the consistency effect was inverse for subtraction. Critically, these results were more salient in the less successful problem solvers than their more successful peers. Our study is the first to demonstrate lexical consistency effect on arithmetic neural networks are modulated during reading word problem that required distinct arithmetic operations. More broadly, our study has strong potentials to add linkage between neuroscience and education by remediating deficits and enhance instruction design in the school curriculum.